Resistance, chaos and control in China Taiping rebels, Taiwanese ghosts and Tiananmen - Weller, Robert P. (Univ. of Washington Press, 1994)
The material on the Taiping Rebellion offers new views of the role of spirit possession in the movement, and the section on surging ghost worship in Taiwan addresses the reproportioning of religion as the island's economy and political structure have been transformed in the last two decades. The Tiananmen chapters examine the nature of cultural control and resistance in China and other socialist societies
Keywords: Dissidenten; Geschichte; Ghosts -- Taiwan; Kulturwandel; Widerstand; China -- History -- Taiping Rebellion, 1850-1864; China -- History -- Tiananmen Square Incident, 1989; China; Fallstudiensammlung